Translation Shifts of Noun Phrases in Black Novel - Gita Maharani Kristina Kattu; I Nyoman Udayana; Ketut Artawa (CV. Ulil Albab Corp, 2023)
The title of this study is translation shifts of noun phrases in black cat novel. This study focused on the analysis of the translation shifts of noun phrases found in the black cat novel by Edgar Allan Poe. There are two aims of this study. First, it is to find whether there is a translation shifts that appears in the novel entitled Black Cat by Edgar Allan Poe. Second, it is to describe what kind of translation shifts that occurs in the process of translation. The data in this study were taken from the black cat novel by Edgar Allan Poe. In this study, the data that will be presenting by column and after that will be discussed one by one. There are twenty data that will be analyzed. In this study, the method to collect the data were doing a library research. The method and technique of analyzing data in this study is qualitative research. The data analysis will be done by classifying the word or sentences in the novel. The theory used to support the writer to analyze the data is a translation shifts theory by Catford (1965). The result shows that the translation shifts was occurs in the novel entitle Black Cat. There are only four types of translation shifts that occurs in the novel. First is structure shift. The second shift that occurs on the novel is class shift. In the cast of this shift there are possibility of a change in word class. It can be noun to verb, verb to noun, verb to adjective, adjective to adverb and vice versa. The third shift that showed in the data is unit/rank shift. The last shift that occurs in the novel entitle the black cat is intra system shift.